Nilai Perusahaan pada Industri Consumer Non-Cyclicals: Peran Profitabilitas, Leverage, dan Ukuran Perusahaan Periode 2021-2024 - Priskila Septyan Anggriyani; Andhika Ryan Priyatam; Dian Prawitasari; Vicky Oktavia; Suhita Whini Setyahuni (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the factors influencing firm value in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Using a quantitative approach, the analysis is conducted on 100 observations obtained from 25 selected companies. Firm value is assessed using Tobin’s Q, while the independent variables consist of profitability measured by Return on Assets (ROA), leverage proxied by the Debt to Equity Ratio (DER), and firm size calculated as the natural logarithm of total assets. The empirical results indicate that profitability and leverage individually exert a positive and significant effect on firm value, whereas firm size does not show a significant influence. Nevertheless, simultaneous testing validates that these three predictors collectively have a significant impact. These findings highlight that internal financial metrics, specifically profit efficiency and debt strategy, are crucial drivers of firm valuation. This research aims to provide investors with a comprehensive overview to evaluate a company's profitability and leverage prior to making investment decisions.